One pot synthesis of hybrid ZnS–Graphene nanocomposite with enhanced photocatalytic activities using hydrothermal approach - Sagadevan, Suresh; Chowdhury, Zaira Zaman; Johan, Mohd Rafie; Rafique, Rahman Faizur; Aziz, Fauziah Abdul (Springer, 2018)
In this work, a facile, one pot hydrothermal approach was undertaken to synthesize ZnS/Graphen hybrid nanocomposites. X-ray powder diffraction analysis was carried out to identify the structure and crystalline phase of the prepared sample. Scanning electronic microscopic analysis (SEM) was carried out to observe the surface texture and the Particle shape and size of the developed nanocomposite samples were analyzed using Transmission electronic microscopic analysis (TEM). The elemental composition of the prepared sample was determined using EDS spectrum. The functional groups for pure and ZnS coated Graphene nanocomposites were confirmed using FTIR spectrum. The peak shifts for the individual composite materials were observed using Raman spectroscopic analysis. The optical properties of the samples were examined using UV–Vis reflectance and photoluminescence spectroscopic analysis (PL). The sample showed enhanced photocatalytic performance compared to pure ZnS which is attributed to the reduction of photoinduced electron–hole pair recombination persuaded by incorporation of nanoporous graphene inside the nanocomposite matrix.